Settlement pattern of Posidonia oceanica epibionts along a gradient of ocean acidification: an approach with mimics - DONNARUMMA, L.; LOMBARDI, C.; COCITO, S.; GAMBI, M.C. (Mediterranean Marine Science, 2014)
Effects of ocean acidification (OA on the colonization/settlement pattern of the epibiont community of the leaves and rhizomes of the Mediterranean seagrass, Posidonia oceanica , have been studied at volcanic CO 2 vents off Ischia (Italy), using “mimics” as artificial substrates. The experiments were conducted in shallow Posidonia stands (2-3 m depth), in three stations on the north and three on the south sides of the study area, distributed along a pH gradient. At each station, 4 rhizome mimics and 6 artificial leaves were collected every three months (Sept 2009-Sept 2010). The epibionts on both leaf and rhizome mimics showed clear changes along the pH gradient; coralline algae and calcareous invertebrates (bryozoans, serpulid polychaetes and barnacles) were dominant at control stations but progressively disappeared at the most acidified stations. In these extremely low pH sites the assemblage was dominated by filamentous algae and non calcareous taxa such as hydroids and tunicates. Settlement pattern on the artificial leaves and rhizome mimics over time showed a consistent distribution pattern along the pH gradient and highlighted the peak of recruitment of the various organisms in different periods according to their life history. Posidonia mimics at the acidified station showed a poor and very simplified assemblage where calcifying epibionts seemed less competitive for space. This profound difference in epiphyte communities in low pH conditions suggests cascading effects on the food web of the meadow and, consequently, on the functioning of the system